J Diabetes Metab 2019
DOI: 10.35248/2155-6156.19.10.832
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycemia and Dyslipidemia Models in Nonhuman Primates: Part IV. Pancreatic Beta Cell Dysfunction and Diabetes Progression

Abstract: OPEN ACCESS Freely available online J ou rna l o f D ia be tes & M e ta bolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…The higher baseline and net AUC of glucose in hyperglycemic group relative to normoglycemic group may indicate more glucose intolerance in the hyperglycemic group. This is consistent with a previous report in cynomolgus monkeys with naturally occurring diabetes 32 , 34 . Both insulin and C-peptide trended lower than basal levels in obese hyperglycemic than normoglycemic group at the 300 min blood sample collection, while glucose levels at 300 min were not different between the two groups.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The higher baseline and net AUC of glucose in hyperglycemic group relative to normoglycemic group may indicate more glucose intolerance in the hyperglycemic group. This is consistent with a previous report in cynomolgus monkeys with naturally occurring diabetes 32 , 34 . Both insulin and C-peptide trended lower than basal levels in obese hyperglycemic than normoglycemic group at the 300 min blood sample collection, while glucose levels at 300 min were not different between the two groups.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study the MMTT plus acetaminophen caused insignificant rise in blood glucose at 30 min measurement accompanied with significant increases in plasma insulin, C-peptide, aGLP-1, tGIP and TG after the meal administration. Baseline levels of overnight fasted glucose and insulin, time courses and AUCs of glucose and insulin for obese hyperglycemic and normoglycemic groups are consistent with reported data in cynomolgus monkey model of spontaneously developed diabetes 32 , 34 . It has been reported that fasted blood glucose > 125 mg/dL (> 7 mmol/L) represents progression from prediabetes to overt diabetes, and this could be hastened in NHPs by feeding the monkeys a high fat high glucose or high-sugar diets 44 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation